Animal Passions and Beastly Virtues: Reflections on Redecorating Nature - Bekoff, Marc (Animals, culture, and society, 2006)
What is it really like to be a dog? Do animals experience emotions like pleasure, joy, and grief? Marc Bekoff's work draws world-wide attention for its originality and its probing into what animals think about and know as well as what they feel, what physical and mental skills they use to live successfully within their social community. Bekoff's work, whether addressed to scientists or the general public, demonstrates that investigations into animal thought, emotions, self-awareness, behavioral ecology, and conservation biology can be compassionate as well as scientifically rigorous.In Animal Passions and Beastly Virtues, Bekoff brings together essays on his own ground-breaking research and on what scientists know about the remarkable range and flexibility of animal behavior. His fascinating and often amusing observations of dogs, wolves, coyotes, prairie dogs, elephants, and other animals playing, leaving and detecting scent-marks ("yellow snow"), solving problems, and forming friendships challenge the idea that science and the ethical treatment of animals are incompatible.